Investigating Key Determinants for the Success of Knowledge Management System (KMS) in Higher Learning Institutions of Malaysia using Structural Equation Modeling - Yuserrie, Zainuddin; Noor Azlinna, Azizan; Panigrahi, Shrikant (Globeedu Group, 2014)
Implementation of KMS has increased rapidly due to rapid advancement in technology up gradation and usage. After thorough review of previous literatures on KMS, it was noticed that knowledge quality, system quality and service quality are key determinants for KMS success. This study investigates the key determinants for the success of knowledge management system (KMSs) in the higher learning institutions (HLIs) of Malaysia. This paper utilized these key determinants for the investigation of KMS success contributing user satisfaction as mediating effect between key determinants and KMS success. Using the data of 223 respondents engaged with administrative and academic activities in universities and colleges of Malaysia, the relationship between knowledge quality, system quality, and service quality with KMS success using user satisfaction as mediating effect was examined through structural equation modeling. From the structural model it was found that user satisfaction plays a full mediating effect between key determinant factors (knowledge quality, system quality, and service quality) and KMS success. KMS success model generated in this study had provided both applied and theoretical recommendation